Fractionation of the antioxidant and hepatoprotective components of Averrhoa carambola L., (Fam. Oxalidaceae) fruits and leaves - Dela Cruz, Earnest Caiser Q.
Averrhoa carambola L. from the family Oxalidaceae is a perennial plant easily cultivated in tropical and sub-tropical climates. It has diverse traditional uses which stems from the presence of antioxidants in fruits which can act as hepatoprotective agents. Objectives: This study aims to evaluate the antioxidant and hepatoprotective activities of the fractions of Averrhoa carambola L., Fam. Oxalidaceae (Common Name: Balimbing) fruts and leaves. Methodology: Averrhoa carambola L. fruits and leaves were subjected to extraction and modified Kupchan partitioning; using ethyl acetate, dichloromethane, n=hexane and methanolic solution as solvents for fractionation. The obtained fractions were then subjected to phytochemical screening and in vitro DPPH assay. The fractions exhibiting the highest antioxidant activity was then subjected to in vivo liver enzyment assay with gross and histopathological analysis of liver samples. Results: Phytochemical analysis detected flavonoids in the aqueous fruit and leaf fractions, which had the highest antioxidant activities among others. The aqueous fruit fraction exhibited hepatoprotective activity which is not significantly diferent with that of n-acetycysteine (positive control)while the aqueous leaf did not. Conclusion and Recommendations: The aqueous fractions of both the fruits and leaves exhibited the highest free radical scavening activities among all the fractions. The activities of the above mentioned fractions were further evaluated for their ability to protect the liver from acetaminophen-induced hepatoxicity and the aqueous fruit fraction demonstrated hepatoprotective acativity against acetaminophen. It is recommended to revalidate the results of the liver enzyme levels of Treatment Group C, to strengthen the conclusion of the study. Further fractionation of the aqueous fruit fraction is also recommended to isolate the possible compounds responsible for the detected activities.